Contribution of the histone variant H2A.Z to expression of responsive genes in plants. (15th February 2023) - Long, Jiaxin; Carter, Benjamin; Johnson, Emily T.; Ogas, Joe
Abstract: The histone variant H2A.Z plays a critical role in chromatin-based processes such as transcription, replication, and repair in eukaryotes. Although many H2A.Z-associated processes and features are conserved in plants and animals, a distinguishing feature of plant chromatin is the enrichment of H2A.Z in the bodies of genes that exhibit dynamic expression, particularly in response to differentiation and the environment. Recent work sheds new light on the plant machinery that enables dynamic changes in H2A.Z enrichment and identifies additional chromatin-based pathways that contribute to transcriptional properties of H2A.Z-enriched chromatin. In particular, analysis of a variety of responsive loci reveals a repressive role for H2A.Z in expression of responsive genes and identifies roles for SWR1 and INO80 chromatin remodelers in enabling dynamic regulation of H2A.Z levels and transcription. These studies lay the groundwork for understanding how this ancient histone variant is harnessed by plants to enable responsive and dynamic gene expression (Graphical Abstract). Graphical Abstract: ga1